Tanaididae (Crustacea, Tanaidacea, Tanaidomorpha, Tanaidoidea) on a Floating Dock, West Beach, Adelaide, South Australia: Introduced or Indigenous? - Tait, Valerie K.; Conlan, Kathleen E.; Dittmann, Sabine (Zootaxa, 2021)
Floating artificial structures provide sites for fouling communities and favourable habitat for the establishment of non-indigenous species. Two species of Tanaididae dominated crustacean biota in a one year time-series sampling of macroalgae on the floating dock at the West Beach boat ramp, Adelaide, South Australia. This paper provides identifications for these two species and discusses inter- and intra-species variability considering the available body of morphological and molecular information. We have given one species a new species designation, Tanais adelaidensis n. sp. The other has a 655 nucleotide CO1 sequence matching that of Hexapleomera sasuke Tanabe & Kakui, 2019 collected in Japan, also matching a shorter CO1 sequence for a described Zeuxo Templeton, 1840 species from the Eastern Mediterranean. This work underlines the utility and need for detailed morphological and molecular data to resolve the taxonomy and biogeography of fouling and holdfast community tanaids, particularly those that have the demonstrated potential for a history of transport between geographically distant sites.